Implementation of Accelerated Complete Systematic Land Registration in 2019 in Grabagan Village, Sidoarjo : Implementasi Percepatan Pendaftaran Tanah Sistematis Lengkap Tahun 2019 Di Desa Grabagan, Sidoarjo - Siti Lailatul Mufidah; Sri Budi Purwaningsih (Academia Open, 2020)
The Indonesian government holds Land Registration for the Indonesian people in accordance with the provisions in Government Regulation Number 24 of 1997 concerning Land Registration. One of the Indonesian Government's programs regarding land registration is carrying out a Complete Systematic Land Registration program in 2017 to ensure legal certainty and legal protection for the Indonesian people. This study aims to determine the implementation of accelerated land registration in 2019 in Grabangan Village, Tulangan District, Sidoarjo Regency. This type of research uses social legal research by examining laws and other regulations with a qualitative approach accompanied by interviews and questionnaires to obtain data. The results of this study explain that the complete systematic land registration activities for the Indonesian people that have been carried out by the Sidoarjo Regency Land Office are in accordance with the provisions in the Regulation of the Minister of Agrarian / Spatial Planning for the Head of the National Land Agency Number 12 of 2017, however, in Grabangan Village there are obstacles, for example: lack of Human Resources, lack of awareness of the community and the main number of fields that float around makes implementation in the village a problem.